Search for the decay B0→γγ - Amo Sanchez, Pablo del; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We report the result of a search for the rare decay B0→γγ in 426 fb−1 of data, corresponding to 226×106 B0B[bar]0 pairs, collected on the Υ(4S) resonance at the PEP-II asymmetric-energy e+e− collider using the BABAR detector. We use a maximum likelihood fit to extract the signal yield and observe 21+13−12 signal events with a statistical significance of 1.8σ. This corresponds to a branching fraction B(B0→γγ)=(1.7±1.1(stat.)±0.2(syst.))×10−7. Based on this result, we set a 90% confidence level upper limit of B(B0→γγ)<3.2×10−7.